CONCERNING A SELECTED DIALECT LEXICON FROM THE WORKS KRPEN ŽIVOT AND TOLE PAŠA BY STALE POPOV (Slavic Studies, 2025)
Many Macedonian writers in their works have used words originating from the colloquial language of people without adapting them to the literary language, thereby enriching the vocabulary itself. There is a large fund of dialectally used word forms in the works of the great Macedonian writer Stale Popov, which is why we are devoting our attention to part of the vocabulary used in his works.
Keywords: dialectology; lexicology; dialect words; Stale Popov